Paracoccidioides Genomes Reflect High Levels of Species Divergence and Little Interspecific Gene Flow (2020)
ABSTRACT : The fungus Paracoccidioides is a prevalent human pathogen endemic to South America. The genus is composed of five species. In this report, we use 37 whole-genome sequences to study the allocation of genetic variation in Paracoccidioides. We tested three genome-wide predictions of advanced speciation, namely, that all species should be reciprocally monophyletic, that species pairs should be highly differentiated along the whole genome, and that there should be low rates of interspecific gene exchange. We find support for these three hypotheses. Species pairs with older divergences show no evidence of gene exchange, while more recently diverged species pairs show evidence of modest rates of introgression. Our results indicate that as divergence progresses, species boundaries become less porous among Paracoccidioides species. Our results suggest that species in Paracoccidioides are at different stages along the divergence continuum.